Occult Spinal Dysraphism in the Presence of Rare Cutaneous Stigma in a Neonate: Importance of Ultrasound and Magnetic Resonance Imaging. (23rd May 2013) - Pires, Claudio Rodrigues; Medeiros, Jane Marília Matos de; Araujo Júnior, Edward; Czapkowski, Adriano; Zanforlin Filho, Sebastião Marques
Abstract : Occult spinal dysraphism is defined as a group of dystrophic conditions below an intact cover of dermis and epidermis. Ultrasonography using linear transducers is a fast, inexpensive, and effective method that makes it possible to view the content of the vertebral canal and bone structures. Magnetic resonance imaging (MRI) is reserved for elucidating the type of dysraphism and for planning corrective surgery. We present a case of a five-day-old female neonate who presented cutaneous stigmas (in the lumbar region, hands, and feet), in whom ultrasonography demonstrated dysraphism in the lumbar region. MRI confirmed the type of dysraphism and enabled surgical planning.